Conventional masonry and light steel framing comparative analysis: a case study in unifammary residence in Teófilo Otoni, MG - Salomão, Pedro Emílio Amador (2019)
The search for constructive alternatives that are more efficient, sustainable and fast in order to increase productivity and to meet the increasing demand of the Market has been one of the great challenges for the construction industry. In order to meet this demand a new construction method known as Light Steel Framing (LSF) has been a great alternative, although it is better known in  developed countries in Brazil, its practice has been diffused and used gaining even more space in the providing a fast and quality construction. In this work a comparative analysis was performed between the Light Steel Framing system and Conventional Masonry through a project of a model house of a floor with the objective of presenting the main differentials between these constructive systems in single family homes. With the projects defined, a quantitative survey of the materials used is done and the compositions of the main elements that differ between both systems are assembled. Through the surveys it was possible to identify the unit costs of each item and to carry out an analysis of the results obtained highlighting the main differences. The results showed that the LSF system presents as an industrialized system presenting higher productivity, having a clean, dry, and sustainable construction, besides presenting low weight, however, in relation to the cost of the work, the study presented the LSF system as less advantageous when compared to conventional masonry, presenting 18,09% more expensive. Knowing that the Light Steel Framing system has so many technical advantages with greater feasibility of execution over the conventional masonry system already proven with this study, it is concluded that professionals in the field of construction should encourage more entrepreneurs and contractor to use this type of construction.